Expert System for Stunting Diagnosis in Children Using Certainty Factor Method - Laku, Veren Verin Valery; Hasan, Patmawati; Pawan, Elvis (International Journal of Applied Research and Sustainable Sciences, 2024)
The development of information technology has affected many aspects of life, including health and education. In Puskesmas Kotaraja, Jayapura, Indonesia, the diagnosis of stunting disease has become a major focus. With the rise in stunting cases following the COVID-19 pandemic, efficient solutions are needed. Specialized systems with certainty factor methods offer accurate and efficient alternatives. This research builds a specialist system to detect stunts in children based on their experience and beliefs. Through previous system testing and problem analysis, this method has proven to be effective in providing accurate diagnostic solutions with a 98.74 degree of confidence. It is expected that this system will help improve the quality of health care in the puskesmas and reduce the cost of patient consultation